2017
DOI: 10.1002/adma.201605307
|View full text |Cite
|
Sign up to set email alerts
|

Shape Controlled Hierarchical Porous Hydrophobic/Oleophilic Metal‐Organic Nanofibrous Gel Composites for Oil Adsorption

Abstract: A versatile and facile synthetic route toward a ultralight hierarchical poroushybrid composed of metal-organic gels and fluorinated graphene oxide is reported. The composite gels show excellent absorbency of oil and various organic solvents due to their prominent meso/macropores, notable hydrophobicity, and superoleophilicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
116
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 165 publications
(119 citation statements)
references
References 53 publications
2
116
0
Order By: Relevance
“…A promising class of novel systems are 2D inorganic-organic hybrid materials derived from crystalline coordination networks, in particular from metal-organic frameworks (MOFs). [11][12][13][14][15] In general, MOFs are based on the self-assembly of metal 2D layered materials, including metal-di-chalcogenides and transition metal layered double hydroxides, among others, are intensively studied because of new properties that emerge from their 2D confinement, which are attractive for advanced applications. Herein, 2D cobalt ion (Co 2+ ) and benzimidazole (bIm) based zeolite-imidazole framework nanosheets, ZIF-9(III), are reported as exceptionally efficient electrocatalysts for the oxygen evolution reaction (OER).…”
mentioning
confidence: 99%
“…A promising class of novel systems are 2D inorganic-organic hybrid materials derived from crystalline coordination networks, in particular from metal-organic frameworks (MOFs). [11][12][13][14][15] In general, MOFs are based on the self-assembly of metal 2D layered materials, including metal-di-chalcogenides and transition metal layered double hydroxides, among others, are intensively studied because of new properties that emerge from their 2D confinement, which are attractive for advanced applications. Herein, 2D cobalt ion (Co 2+ ) and benzimidazole (bIm) based zeolite-imidazole framework nanosheets, ZIF-9(III), are reported as exceptionally efficient electrocatalysts for the oxygen evolution reaction (OER).…”
mentioning
confidence: 99%
“…The results indicated the presence of an adsorption competition between water and toluene in the adsorbents. Many studies have also shown the great potential of hydrophobic MOFs or their derived materials for bulk oil/water separation and bulk oil adsorption from water for the cleanup of oil spills . The removal of other types of harmful or useful gases or organic substances, such as ethylene, acetic acid, thiophene, peptides, aromatic amino acids, and pharmaceuticals, from air or water by hydrophobic MOFs and their derived materials has also been documented.…”
Section: Potential Applicationsmentioning
confidence: 99%
“…To date, the synthetic strategies toward this aim include: i) forming mixed matrix membranes by doping pre‐synthesized MOFs; ii) forming metal–organic gels through sol–gel processes; and iii) employing 2D/3D structured supports for loading MOF particles . However, these approaches lack control over the organization of the MOFs inside the support, resulting in severe MOF aggregation, low MOF contents (usually <30 %), ill‐defined hierarchical porosity, and poor formability of the support.…”
Section: Introductionmentioning
confidence: 99%